Development of focusing grating couplers for lithium niobate on insulator platform. (December 2020) - Elmanov, I; Sardi, F; Xia, K; Kornher, T; Kovalyuk, V; Prokhodtsov, A; An, P; Kuzin, A; Elmanova, A; Goltsman, G; Kolesov, R
Abstract: In this paper, we fabricate and experimentally study focusing grating couplers for lithium niobate on an insulator photonic platform. The transmittance of a waveguide equipped with in- and out-couplers with respect to the grating period is measured with and without silicon dioxide cladding applied. Our results show the influence of silicon dioxide cladding on the efficiency and the central wavelength of grating couplers and can be used to improve grating coupling efficiency. Our study is supported by numerical simulations.